Association between the L55M and Q192R polymorphisms of the paraoxonase-1 gene and age-related macular degeneration: a meta-analysis - Elguezabal-Rodelo,Rebeca G. (2021)
ABSTRACT Purpose: Paraoxonase-1 activity is associated with age-related macular degeneration. Two polymorphisms (L55M and Q192R) were shown to increase paraoxonase-1 activity and have been implicated in the development of age-related macular degeneration. The results of studies that have examined these polymorphisms are conflicting, showing no effect, as well as increased or decreased risk. Therefore, this meta-analysis was conducted to determine the effect of these polymorphisms on age-related macular degeneration. Methods: PubMed, EBSCO, LILACS, and Scopus databases, as well as and the retrieved bibliographies of publications were searched for case-control studies that examined for paraoxonase-1 polymorphisms and age-related macular degeneration. Data were analyzed using the Comprehensive Meta-Analysis Version 2.2 and the NCSS Statistical Version 2020 software. Genotype distributions were extracted and, depending on the level of heterogeneity, fixed effects or random effects models were used to calculate pooled odds ratios (ORs) with 95% confidence intervals (95% CIs) for the heterozygous, homozygous, dominant, recessive, and allelic genetic models. Results: Overall, for the L55M polymorphism, none of the genetic models demonstrated a significant association. However, for non-Asian populations, a significant association was determined for the heterozygous and dominant genetic models (ORrange=1.24-1.27, p<0.05). For the Asian population, the heterozygous, dominant, and allelic genetic models demonstrated a benefit/protective factor (ORrange=0.29-0.35, p<0.05). For the Q192R polymorphism, none of the genetic models demonstrated a significant association. However, when the cohort was grouped by ethnicity, a significant association was determined in the Asian population for the recessive and allelic genetic models (ORrange=1.63-2.08, p<0.05). However, for the non-Asian population, there was no association observed. Also, there was no identifiable risk when the cohort was stratified into exudative and non-exudative cases. Conclusions: The paraoxonase-1L55M polymorphism increases the risk of developing age-related macular degeneration in non-Asian populations, whereas in Asian populations, the polymorphism exerts a protective effect. However, for the paraoxonase-1 Q192R polymorphism, only the Asian population demonstrated a risk of developing age-related macular degeneration.